Relationship between DTI-MRI derived metrics and radiotherapy dose range in the contralateral cerebrum in lower grade glioma - Kłos, Justyna; Dijkstra, Hildebrand; van der Weide, Hiska L.; Potze, Jan H.; Sinnige, Peter F.; Ng Wei Siang, Kelvin; Dierckx, Rudi A. J. O.; Borra, Ronald J. H.; Kramer, Miranda C. A.; van der Hoorn, Anouk (Frontiers in Oncology, 2025)
Background and purposeTo evaluate the value of diffusion tensor imaging (DTI) MRI derived fractional anisotropy (FA) and apparent diffusion coefficient (ADC) for both white matter (WM) and grey matter (GM) of the contralateral cerebrum following radiotherapy (RT) for supratentorial lower grade glioma (LGG) as markers for radiotherapy-induced brain damage (RIBD).Materials and methods14 patients were analysed. WM and GM were segmented using automated software (cNeuro) and the mean FA and ADC were extracted per RT dose bin (0-10, 10-20, 20-30, 30-40, 40-50, >50 Gy) of WM and GM. One way ANOVA with post-hoc Bonferroni’s test were used to analyse differences in FA and ADC between dose bins. Fluid-attenuated inversion recovery (FLAIR) hyperintensities were segmented in a semi-automated manner and correlated with a percentual difference in ADC and FA between dose bin ≥50 Gy and the mean of lower dose bins. Furthermore, the correlation of raw values of these 3 metrics within dose bins was explored, and potential relations of changes to clinical parameters.ResultsWe observed changes in FA of WM for dose bin >50 Gy [(F(5, 74) = 5.461, p=0.0002)], but no changes in FA of GM and no changes in ADC for both WM and GM. The percentual change in ADC and FA in WM of dose bin >50 Gy did not correlate with the total volume of FLAIR hyperintensities of the contralateral cerebrum, and also the raw values of these metrics did not correlate within the >50 Gy dose bin, and only correlated with the Total Radiotherapy Dose delivered to the supratentorial brain.ConclusionIn the late phase after RT for LGG (average > 3 years), DTI-MRI derived FA values decreased significantly in WM in the cerebrum contralateral to the tumour, while no changes were observed in GM or in ADC values. The FA decrease is only observed in areas receiving the highest RT dose, allows for a localized assessment in the individual patient, and is not correlated with the observed total load of FLAIR hyperintensities within the contralateral cerebrum or changes in ADC, suggesting DTI-MRI and FLAIR derived metrics reflect RIBD in different ways.